ANALISIS PERENCANAAN KRIB (PEMECAH ARUS) SEBAGAI PENGAMAN JEMBATAN RANGKA BAJA MENGGUNAKAN PEMODELAN SMS (SURFACE WATER MODELING SYSTEM) (STUDI KASUS : PENGAMAN JEMBATAN AIR ENIM 3 KABUPATEN MUARA ENIM) - Aprisandie Aprisandie; Kiagus Muhammad Aminuddin; Arie Putra Usman; Karina Natassia (LATERAL: Jurnal Teknik Sipil, 2025)
Current Breaker Structure (Crib) is one of the water building constructions that can overcome the problem of river bank damage, which is caused by river flow experiencing a high increase in flood discharge. Adjustment of the type of grib construction used certainly refers to the location of the grib placement so that it can have a real impact in overcoming the destructive power of river water when there is an increase in flood discharge volume. The purpose of this study is to analyze the planned type of current breaker structure (grib) at the location of the Enim 3 Steel Frame Bridge using the SMS (Surface Modeling System) Modeling method that can provide information on water flow in the watershed. This research method is in the form of research by conducting various mathematical and empirical approaches, so that the type of grib that is appropriate to field conditions (soil, river flow, and facilities around the river) will be obtained which will ultimately produce Design Details that can be followed up with construction activities. From the results of the grib planning calculations, 4 grib units with a hexapod type are obtained which are arranged in a trapezoidal shape.